Implementation of the MBG Program in Synergizing School Health Efforts at SD Mandiri Palembang - Mega Mustika; Edi Harapan; Nurlina Nurlina (Journal of Social Work and Science Education, 2026)
This study aims to describe the implementation of the Free Nutritious Meal Program (MBG) and its operational synergy with the School Health Program (UKS) at SD Mandiri Palembang, focusing on planning, execution, supervision, and follow-up, while identifying constraints and solutions. Employing a qualitative approach, data were collected through interviews, observations, and documentation. The results show that structured planning based on nutritional mapping and multi-stakeholder coordination enables effective implementation, featuring regular meal distribution and integrated nutrition education. Continuous supervision, including hygiene monitoring and nutritional status checks, strengthens the MBG-UKS synergy. Follow-up actions adapt menus and improve coordination to address challenges such as varying student appetite. The novelty lies in empirically illustrating how a feeding program can be systematically integrated into a school health framework within a specific Indonesian context. A key practical implication is the provision of a replicable implementation model for other schools seeking to link nutrition and health services. The study contributes a detailed qualitative case study to the field of school health management, demonstrating that structured processes and cross-program collaboration are essential for sustaining integrated student well-being initiatives.